Declining prevalence of hepatitis A virus antibodies among children from low socioeconomic groups reinforces the need for the implementation of hepatitis A vaccination in Brazil - Vitral, Claudia Lamarca (2012)
Universidade Federal Fluminense. Departamento de Microbiologia e Parasitologia. Niterói, RJ, Brasil / Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Desenvolvimento Tecnológico em Virologia. Rio de Janeiro, RJ, Brasil.